RACISM IN WHERE’S THE MONEY(2017) MOVIE - Jeanniefer Sholihati; Arry Purnama (CALL, 2021)
Racism still needs attention because it still happens until now. Where’s the Money is attractive popular movie about black people so that this research focuses on exploring the kind of racism in Where’s the Money (2017) movie to get a closer look at some kinds of coming from the action and/or dialogue. The main objective of this research is to determine the forms of racism. The researchers employed Mark Harlsted’s theory of racism by literary criticism and an objective approach. This research is also framed in a qualitative descriptive method in collecting the data. The result shows that racial discrimination often occurs in the movie. There are three types of racial discrimination found in the movie: Pre-reflected Gut Racism, Cultural Racism, and Institutional Racism. The findings are ten data showing Pre-reflected Gut Racism, eight data exhibiting Cultural Racism, and three data displaying Institutional Racism. The three data that have been collected and listed are those that have been classified based on their form and types, and also analyzed according to the approach and theories. Based on the findings, it can be seen that Whites give opportunity to a Black to join his community only for their own advantages. That is, to make a good image in the society as open-minded individuals concerning the racial issues. Most people say that racism does no longer exist, but the reality makes different views. In the US, Black Lives Matter is one of the movements which becomes a great issue and very crucial, which is also related to racial topic. Keywords: Racial Discrimination; Racism; Movie; Pre-reflected Gut Racism;     Cultural Racism; Institutional Racism